Edukasi Pengenalan Akad Dalam Transaksi Syariah Serta Pengenalan Pembiayaan Syariah Online Guna Penguatan Modal Bagi Para Pelaku UMKM Di Desa Sebewe Kecamatan Moyo Utara - Hanifa Sri Nuryani; Sudrajat Martadita; Fadli Faturrahman; edi edi (AMMA : Jurnal Pengabdian Masyarakat, 2022)
This community empowerment activity was carried out in Sebewe Village, North Moyo District, Sumbawa Regency. Based on the results of community service activities with the theme "Education on the introduction of contracts in sharia transactions and the introduction of online sharia financing to strengthen business capital for small and medium business actors in Sebewe Village, North Moyo District, Sumbawa Regency" which has been carried out, it can be concluded as follows: 1). The participants already have additional information about sharia-based online loan institutions that are recognized by the Indonesian Financial Services Authority. 2) The participants of small and medium businesses get information about the types of contracts in sharia transactions as well as accurate tricks to qualify for loans in sharia banking. 3) Small and medium enterprises in Sebewe Village know how to do simple bookkeeping.